Cider made simple : all about your favorite new drink - Alworth, Jeff (Chronicle Books, 2015)
Provides details on every aspect of cider making, from the choice of apple to the process of distilling and bottling, interviewing brewers around the world to create a guide for the best ciders from Spain, England, Canada, France, and the US.